Jejak Spiritualitas Dalam Dialog Aktivis Perdamaian Di Kabupaten Jember Jawa Timur - As'ari; Rozzaq, Abd. (Spiritualita, 2024)
This study explores the experiences of Muslim and Christian peace activists in Jember, Indonesia, in fostering interfaith dialogue rooted in the pursuit of inner meaning and universal human values. Within Indonesia’s multicultural context, which often grapples with social fragmentation, the research reveals how both communities employ spiritual wisdom as a foundation for reconciliation, transcending formal theological differences. Utilizing a qualitative approach, the findings demonstrate that interfaith dialogue in Jember extends beyond the exchange of perspectives to include collective immersion into the esoteric dimensions of religion—such as reflections on humility, compassion, and awareness of transcendent unity. Barriers like historical conflicts and divergent interpretations of sacred texts are mitigated through practices of silaturahmi hati (heartfelt spiritual kinship), where Muslim activists embrace the principle of mahabbah (universal love), while Christian counterparts draw on parallel contemplative traditions. The study concludes that interreligious harmony in Jember emerges not from doctrinal uniformity but from a commitment to nurturing hidden threads of spiritual light woven through its diverse societal fabric.